Experimental investigation and thermodynamic calculations of the Bi-Ni-Pb phase diagram - Minic, Dusko; Premovic, Milena; Toskovic, Nemanja; Manasijevic, Dragan; Cosovic, Vladan; Janackovic, Marija; Tomovic, Milica (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The article presents an experimental study of a phase diagram of a ternary Bi-Ni-Pb system using differential thermal analysis (DTA), scanning electron microscopy (SEM) with energy dispersive spectrometry (EDS) and X-ray powder diffraction (XRD) analysis. The investigated ternary alloys were selected from three vertical sections (x(Bi)=0.75, x(Ni)=0.1 and x(Pb)=0.9) and two isothermal sections at 100 and at 300 °C. The obtained experimental results were compared with the thermodynamically extrapolated phase diagram of the Bi-Ni-Pb ternary system based on the thermodynamic parameters for the constitutive binary systems available in literature. Reasonably close agreement between the experimental data and the calculated phase diagram was obtained.